Comparative acetylomic analysis reveals differentially acetylated proteins regulating anther and pollen development in kenaf cytoplasmic male sterility line. Issue 4 (6th March 2019) - Chen, Peng; Wei, Fan; Li, Ru; Li, Zeng‐Qiang; Kashif, Muhammad H.; Zhou, Rui‐Yang
Abstract : Cytoplasmic male sterility (CMS) is widely used in plant breeding and represents a perfect model to understand cyto‐nuclear interactions and pollen development research. Lysine acetylation in proteins is a dynamic and reversible posttranslational modification (PTM) that plays an important roles in diverse cell processes and signaling. However, studies addressing acetylation PTM regarding to anther and pollen development in CMS background are largely lacking. To reveal the possible mechanism of kenaf ( Hibiscus cannabinus L.) CMS and pollen development, we performed a label‐free‐based comparative acetylome analysis in kenaf anther of a CMS line and wild‐type (Wt). Using whole transcriptome unigenes of kenaf as the reference genome, we identified a total of 1204 Kac (lysin acetylation) sites on 1110 peptides corresponding to 672 unique proteins. Futher analysis showed 56 out of 672 proteins were differentially acetylated between CMS and Wt line, with 13 and 43 of those characterized up‐ and downregulated, respectively. Thirty‐eight and 82 proteins were detected distinctively acetylated in CMS and Wt lines, respectively. And evaluation of the acetylomic and proteomic results indicated that the most significantly acetylated proteins were not associated with abundant changes at the protein level. Bioinformatics analysis demonstrated that many of these proteins were involved in various biological processes which may play key roles in pollen development, inculding tricarboxylic acid (TCA) cycle and energy metabolism, protein folding, protein metabolism, cell signaling, gene expression regulation. Taken together, our results provide insight into the CMS molecular mechanism and pollen development in kenaf from a protein acetylation perspective.